Counseling on paying zakat as a deduction from income tax in Sukosari Village, Bandongan, Magelang Regency - Nur Rofiq; Yulia Eko Susilowati; Rr. Yunita Puspandari (Community Empowerment, 2022)
Zakat is the third pillar of Islam that all Muslims must follow. Meanwhile, taxes are one of the most important sources of revenue for the Indonesian government, with income tax (PPh) being one of them. Therefore, Indonesian Muslims are required to pay both, taxes and zakat, known as dual responsibility. In Sukosari Village, Bandongan District, Magelang Regency, this program is carried out in the form of counseling and simulation using lecture, discussion, and practice methods. As a result of the community service, participants able to demonstrate the zakat mechanism as a income tax (PPh) deduction. Furthermore, residents of Sukosari Village, in particular, can avoid double taxation (the obligation to pay zakat and taxes).